2011
DOI: 10.1016/j.healun.2011.01.708
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunity-induced autoimmunity as a potential mechanism in the pathogenesis of chronic rejection of human lung allografts

Abstract: Background Bronchiolitis obliterans syndrome (BOS) is a major cause of morbidity and mortality post lung transplantation (LTx). We sought to determine the relationship between alloimmune responses and autoimmunity, and subsequently how autoimmunity leads to chronic rejection. Methods We analyzed the development of donor specific antibodies (Abs) in LTx by flow PRA and the development of Abs to K-α1 tubulin (K-α1T) and collagen V (ColV) by ELISA. The frequency of K-α1T and ColV specific T cells that secrete I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
163
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(175 citation statements)
references
References 33 publications
9
163
0
3
Order By: Relevance
“…Elicitation of immune responses to the mismatched donor human leukocyte antigen (HLA) and breakdown of tolerance to tissue-restricted self-antigens pose a significant challenge to acceptance and continued graft function following organ transplantation (67,68). While the mechanisms of AMR are not firmly established, de novo donor-specific antibodies against HLA have been shown to predispose to the development of immune responses to lung self-antigens and BOS (69)(70)(71). To define mechanisms leading to anti-MHC-mediated development of rejection, a preclinical murine model was developed in which exogenous anti-MHC was administered into the native lungs and elicited production of antibodies and T cell responses specific for lung-associated self-antigens, type V collagen [col(V)], and K-α 1 tubulin, culminating in fibrotic pathology (72,73).…”
Section: Armentioning
confidence: 99%
“…Elicitation of immune responses to the mismatched donor human leukocyte antigen (HLA) and breakdown of tolerance to tissue-restricted self-antigens pose a significant challenge to acceptance and continued graft function following organ transplantation (67,68). While the mechanisms of AMR are not firmly established, de novo donor-specific antibodies against HLA have been shown to predispose to the development of immune responses to lung self-antigens and BOS (69)(70)(71). To define mechanisms leading to anti-MHC-mediated development of rejection, a preclinical murine model was developed in which exogenous anti-MHC was administered into the native lungs and elicited production of antibodies and T cell responses specific for lung-associated self-antigens, type V collagen [col(V)], and K-α 1 tubulin, culminating in fibrotic pathology (72,73).…”
Section: Armentioning
confidence: 99%
“…Abnormal epithelial repair eventually causes an epithelial-to-mesenchymal transition (EMT), a functional and phenotypic change of epithelial cells into spindle-shaped, migratory (43) and matrix-component-secreting mesenchymal cells (10, 41), and a process associated with lung fibrosis (15,27). However, the direct connection between EMT and the in vivo phenomena of fibrosis and fibro-obliterative disease remains controversial.We and others previously reported that OB is associated with dysregulation of two types of collagen: 1) marked increase in type V collagen [col(V)], a quantitatively minor lung collagen (8,14,40), and 2) a decrease in the major lung collagen type I [col(I)] (2, 53). We have shown that prospective monitoring of patients with human lung transplant revealed a critical role of col(V)-specific cellular immunity in OB pathogenesis (14,40).…”
mentioning
confidence: 99%
“…We and others previously reported that OB is associated with dysregulation of two types of collagen: 1) marked increase in type V collagen [col(V)], a quantitatively minor lung collagen (8,14,40), and 2) a decrease in the major lung collagen type I [col(I)] (2, 53). We have shown that prospective monitoring of patients with human lung transplant revealed a critical role of col(V)-specific cellular immunity in OB pathogenesis (14,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме этого, в ретроспективном исследовании D.Saini et al [77] у пациентов с СОБ, перенесших трансплантацию легких (n = 42), обнаружена тесная корреляция меж ду появлением донор специфических антител к ан тигенам HLA и антител против аутоколлагена (кол лагена V и тубулина К α 1 ).…”
Section: рекомендацияunclassified